Global mapping of Salmonella enterica-host protein-protein interactions during infection - Walch, Philipp; Selkrig, Joel; Knodler, Leigh A.; Rettel, Mandy; Stein, Frank; Fernandez, Keith; Viéitez, Cristina; Potel, Clément M.; Scholzen, Karoline; Geyer, Matthias; Rottner, Klemens; Steele-Mortimer, Olivia; et al. (Cell host and microbe, 2021)
Intracellular bacterial pathogens inject effector proteins to hijack host cellular processes and promote their survival and proliferation. To systematically map effector-host protein-protein interactions (PPIs) during infection, we generated a library of 32 Salmonella enterica serovar Typhimurium (STm) strains expressing chromosomally encoded affinity-tagged effectors and quantified PPIs in macrophages and epithelial cells. We identified 446 effector-host PPIs, 25 of which were previously described, and validated 13 by reciprocal co-immunoprecipitation. While effectors converged on the same host cellular processes, most had multiple targets, which often differed between cell types. We demonstrate that SseJ, SseL, and SifA modulate cholesterol accumulation at the Salmonella-containing vacuole (SCV) partially via the cholesterol transporter Niemann-Pick C1 protein. PipB recruits the organelle contact site protein PDZD8 to the SCV, and SteC promotes actin bundling by phosphorylating formin-like proteins. This study provides a method for probing host-pathogen PPIs during infection and a resource for interrogating STm effector mechanisms.
Gesehen am 14.04.2022